PENINGKATAN KECERDASAN KINESTETIK MELALUI GERAK DAN LAGU PADA ANAK KELOMPOK B DI PAUD TERPADU BON THORIF PALEMBANG - Vinna Patriana; Sri Sumarni; hasmalena hasmalena (Tumbuh Kembang: Kajian Teori dan Pembelajaran PAUD, 2017)
This study aims to improve kinesthetic intelligence through movement and song in child group B in PAUD Integrated Bon Thorif Palembang. The method used in this research is Classroom Action Research (PTK). Subjects in this study were children aged 5-6 years, amounting to 19 children consisting of 11 boys and 9 girls. The research is done in two cycles, each cycle is consist from 3 meetings. Every meeting is done in 4 stages, which is planning, implementation, observation, and reflection. If the number of each cycle hasn’t met the established criteria , which is 15 out of 19 children (75%) that reach the limit of mastery in classical then the research continued the next cycle. Based on the analysis result of the research there’s significant increase in the value’s increase of the children who get the minimal category Developed As Expectation (BSH) in pre-cyecle as many as 4 children (21%) , first cycle is increase to 11 children (58%) and an second cycle increase to 16 children (84%). This is apparent from the dominant indicator appears is the son of actively moving song from begining to end, while the indicators that come up is less flexibility when moving the hand swinging the appropriate song. From the data collected indicate that the presence of kinesthetic intelligence in child group B in PAUD integrated Bon Thorif Palembang after using movement and song.